Biomechanical and physiological determinants of 2km rowing performance on fixed ergometer - Zahiran, Amirah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
The outcomes from this study are important to enhance rowing performance especially for rowers. Based on previous study, many papers focused more on aerobic (V02) and anaerobic (Peak power) in rowing performance but no studies have evaluated the biomechanical determinants of 2km time trial on stationary ergometer. Purpose: This study was conducted to understand the biomechanical and physiological determinants of 2km rowing perfonnance on stationary ergometer. Methods: 10 state-level rowers were recruited (6 males, 4 females) with at least two years experience in competitive rowing. Anthropometric, peak power, blood lactate, heart rate, V02, 20 kinematic motion and stroke rate were recorded during 2km time trial, 30s Wingate anaerobic test and 5 x 4 step test. Pearson's correlation was applied to evaluate the correlation of each physiological, biomechanical and anthropometric variable to the time of 2km rowing completion. Results: Peak power was significantly correlated to the time of 2km rowing completion (r = 0.273; p= 0.044). There was a significantly high correlation of V02 (r = -0.906, p = <0.001) to 2km time trial results. There was a significant correlation between kinematics variables of knee angle at catch (r = -0.376) (p = 0.007) at 1600m and 2000m (r = -0.436; p = <0.00 l ). Positive correlation was found of hip angle at finish during the last sprint of 2000m (r = 0.203; p = <0.00 1) to 2km time trial. Discussion: V02 and peak power showed the significant on correlation of physiological variables during 2km rowing time to completion. Conclusion: The ergometer was a good training tool for the athlete to develop fitness and training. Proper technique of rowing should be emphasised during rowing on stationary ergometer to enhance performance during time trial.